2011
DOI: 10.1002/mus.21822
|View full text |Cite
|
Sign up to set email alerts
|

Time‐course of changes in the myonuclear domain during denervation in young‐adult and old rat gastrocnemius muscle

Abstract: If myonuclear loss initiates muscle wasting, it should precede the loss of muscle mass. As aging affects muscle plasticity, the time-course of muscle atrophy during disuse may differ between young and old animals. To investigate this, gastrocnemius muscles of 5-and 25-month-old rats were exposed to 1, 2, or 4 weeks of denervation, whereas the contralateral gastrocnemius muscles served as controls. Muscle fibers of each type responded similarly to 4 weeks of denervation. For both ages most of the atrophy (36%; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 56 publications
4
46
0
Order By: Relevance
“…This could occur through an effect of SS mitochondria to modulate myonuclear number, as animal models show that SS mitochondria produce more apoptotic stimuli in response to disuse (2), and it has been suggested that loss of myonuclei contributes to muscle atrophy (4). However, we did not observe differences in myonuclei content, in keeping with recent studies showing no loss of myonuclei with disuse (9,67) or modulation of myonuclear number with variation in activity in older men (38). A more plausible mechanism may be via modulation of nuclear function.…”
Section: Discussionsupporting
confidence: 91%
“…This could occur through an effect of SS mitochondria to modulate myonuclear number, as animal models show that SS mitochondria produce more apoptotic stimuli in response to disuse (2), and it has been suggested that loss of myonuclei contributes to muscle atrophy (4). However, we did not observe differences in myonuclei content, in keeping with recent studies showing no loss of myonuclei with disuse (9,67) or modulation of myonuclear number with variation in activity in older men (38). A more plausible mechanism may be via modulation of nuclear function.…”
Section: Discussionsupporting
confidence: 91%
“…As we observed previously [34], the similar muscle mass but larger fibre cross-sectional area in older Gm suggests that the number of fibres was reduced during ageing. This might be the result of an incomplete denervation-reinnervation process leading to loss of fibres [35] and compensatory hypertrophy of the remaining fibres.…”
Section: Effects Of Ageingsupporting
confidence: 86%
“…Sections were co-stained with DAPI and anti-Pax7 antibody according to (van der Meer et al, 2011b). Briefly, sections were fixed in 4% formaldehyde PBS for 10 min, washed with PBST and blocked in 10% normal donkey serum (NDS) in PBS for 30 min.…”
Section: Quantification Of Myonuclei and Sc Numbermentioning
confidence: 99%